Pemberdayaan Siswa Sekolah Dasar Sebagai Duta Kesehatan Melalui Program Dokter Cilik untuk Meningkatkan Kesadaran Hidup Sehat di Lingkungan SD Negeri 1 Aikmel Utara dan Sekitarnya - Zulfadli Hamdi; Muhammad Mirwan Apriandi; Enki Rizaldo; Sapma Dewi Anggraini; Lilik Suriani; Baiq Risa Apriantari; Maeli Astuti (HARAPAN: Jurnal Ilmu Kesehatan dan Psikologi, 2025)
The empowerment of elementary school students as health ambassadors is a strategic effort to enhance awareness of healthy living within schools and surrounding communities. This study aims to examine the effectiveness of the "Little Doctor" program in improving understanding, awareness, and healthy living behaviors at SD Negeri 1 Aik Mel Utara and its surrounding community. The method used is participatory action research, involving students as the primary subjects of the program. The program is designed by providing training to students on basic health, balanced nutrition, hygiene, and first aid. The results of the study show that this program successfully increased students' knowledge of health by up to 85% and encouraged active student participation in disseminating health information to peers and their families. The "Little Doctor" program has proven to be an innovative approach that can be widely implemented to support the creation of a healthy living culture in elementary schools.